The Effectivity of “Pokdarwis” Role on Successfully Marketing of Tourism Village Towards “Mega Tourism: Batu City For The World” - Syarif Hidayatullah; Ike Kusdyah Rachmawati; Umu Khouroh; Irany Windhyastiti; Irany Windhyastiti (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Tourism sector is the one of the leading sectors of Batu City. To enhance the spirit of tourism sector development in the international sphere, in 2017 Government of Batu City launched the slogan